Impact of Grameen Bank Microcredit on Standard of Living in Rural Poor Women in Sariakandi Upazila of Bogra District - Shamim, Md. Abu (American Journal of Trade and Policy, 2019)
The standard of living in many developing countries like Bangladesh especially rural area is not standard level or satisfied. The microcredit programs of Grameen Bank (GB) in Bangladesh have emerged as a strategy on standard of living and reduction poverty. They are also trying to remove poverty and unemployment and energetic poor people who want to engage in economic activities, the institution provides not only loan to them but also advice and monitoring. The aim of the study is to explore the impact of GB microcredit on standard of living of rural women in study area whom have already involved in its loan. As sample only 198 current microcredit fund receiver’s respondents from Sariakandi upazila under Bogra district were selected. Data were collected from six centers under two selected branches using questionnaire. Data were explained normally under descriptive method using simple statistical tools such as chi-square test and One-way ANOVA test and econometric model such as OLS regression. After analyzing data, results of the study show that there has a positive effect on savings, average monthly income, expenditure, average level of education of borrowers’ households, number of income earner and asset. The results of One-way ANOVA test indicate that there exists a significant relationship among some factors of standard of living with amount of loan of GB and Chi-square test is proved that microcredit of GB has also a positive contribution on improving standard of living in study area.
Keywords: Grameen Bank; Microcredit; Standard of Living